Feasibility study of pohon Mas Restaurant air-condationing system - Daniel, Ting Moi Lee. (Universiti Malaysia Sarawak, UNIMAS, 2006)
This research was done to evaluate the ind oor air condition of Poh on Mas R estaurant and find out the source of problem w hich cause d a poor indoor environment of Pohon Mas R estaurant. ASHRAE standard is chosen as standard reference when doing theoretical calculation for ideal cooling load for the restaurant and also field measurement to find out actual value. The study found that ideal cooling load is almost thre e times the actual cooling load and ventilation in actual restaurant condition is only 4.6 percent of ventilation in ideal restaurant condition. Beside s that, ac tual indoor conditions like tempe rature and relative humidity for restaurant are higher than ideal indoor condition s. The study proposed installation of additional exhaust hood ab ove food corner to exhaust smelly air out and additional exhaust fan to exh aust fresh air in to restaurant . Additional air conditioning split units are install to increase the actual cooling load to meet the requirement of ideal cooling load.